2016
DOI: 10.14202/vetworld.2016.118-122
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic, hypolipidemic and antioxidant effects of pioglitazone, insulin and synbiotic in diabetic rats

Abstract: Aim:The objective of the study was to assess the effect of combination treatment of insulin, pioglitazone and synbiotic on streptozotocin (STZ)-induced diabetic rats.Materials and Methods:Diabetes mellitus was induced chemically by intraperitoneal administration of STZ (40 mg/kg b.wt) to male Sprague-Dawley rats. The rats were divided randomly into six groups of six rats in each. Group 1 was maintained as a normal control. Group 2 was maintained as diabetic control; Group 3 was treated with insulin; Group 4 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Verma and Shukla [ 27 ] revealed that L. rhamnosus and L. acidophilus lead to the formation of large quantities of antioxidants, mainly GSH, with inulin being a nondigestible carbohydrate in the small intestine. In another study by Kavitha et al [ 28 ], increased GSH concentrations have been reported due to the combined effects of insulin, pioglitazone, and probiotics in STZ-induced diabetic rats. In a very recent study, the effects of Lactobacillus plantarum HII11 are remarkable in preventing adrenomedullin- (ADM-) mediated colon cancer in the rat [ 29 ].…”
Section: Background and Concept Of Probioticsmentioning
confidence: 99%
“…Verma and Shukla [ 27 ] revealed that L. rhamnosus and L. acidophilus lead to the formation of large quantities of antioxidants, mainly GSH, with inulin being a nondigestible carbohydrate in the small intestine. In another study by Kavitha et al [ 28 ], increased GSH concentrations have been reported due to the combined effects of insulin, pioglitazone, and probiotics in STZ-induced diabetic rats. In a very recent study, the effects of Lactobacillus plantarum HII11 are remarkable in preventing adrenomedullin- (ADM-) mediated colon cancer in the rat [ 29 ].…”
Section: Background and Concept Of Probioticsmentioning
confidence: 99%
“…16 Probiotic, the Greek word, meaning "for life" 19 has been shown to activate monocytes, macrophages, and dendritic cells in vitro that affect the immune system. 20 In addition, prebiotics which are non-digestible carbohydrates consumed by the intestinal bacteria for fermentation, 21 are used in medicine to produce short-chain fatty acids (SCFAs) 22 such as inulin or fructooligosaccharides (FOS), which stimulate the growth and metabolism of probiotics in the intestine. A mixture of prebiotics and probiotics as synbiotic has beneficial effects against several diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, bulk and nanoscale nickel oxide (NiO) have attracted attention for their high stability, [1][2][3][4][5][6][7][8][9] nontoxicity, [5,7] and anomalous chemical, [9][10][11][12] electrochemical, [5][6][7][8][13][14][15][16][17][18][19][20] electronic, [3,21,22] magnetic, [2,9,23] and catalytic [2,4,9,24] and optical [10,13,22,24] properties. NiO nanoparticles (NiONPs), in particular, are used in a variety of fields as electrochemical sensors, [15] biosensors, [6,16] electrochromic windows, [13] gas sensors, [11,12] super capacitor, [17] batteries, [5] fuel cells,…”
Section: Introductionmentioning
confidence: 99%
“…[24] The broad applicability of nanoscale NiO relies on the material's high surface area and interesting properties, including chemical, electrochemical, and catalytic properties, which are not present in the bulk material. To meet the high demand for this nanoscale material, several synthetic methods have been developed based on hydrothermal, [9,11,[14][15][16][24][25][26][27] sol-gel, [4,21,23] hot-injection, [13] co-precipitation, [7] microwave, [2,5] reverse micelle templated, electrochemical [12] and pulsed laser ablation [28] techniques, as well as techniques based on complex formation with an organic moieties and successively their thermal decomposition. [29][30][31][32][33][34] Among the mentioned methods, the latest one is well known as scalable with high yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation